2005
DOI: 10.1152/japplphysiol.01337.2004
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane inhibition reduces an early stage of chronic hypoxia-induced pulmonary hypertension in piglets

Abstract: -The pulmonary vasoconstrictor, thromboxane, may contribute to the development of pulmonary hypertension. Our objective was to determine whether a combined thromboxane synthase inhibitor-receptor antagonist, terbogrel, prevents pulmonary hypertension and the development of aberrant pulmonary arterial responses in newborn piglets exposed to 3 days of hypoxia. Piglets were maintained in room air (control) or 11% O2 (hypoxic) for 3 days. Some hypoxic piglets received terbogrel (10 mg/kg po bid). Pulmonary arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Similar observations were reported earlier that provided evidence for a differential role of endothelium-derived factors on arterial tone in different pathophysiological conditions. Endothelial COX-mediated constrictor, likely to be thromboxane, was shown to be involved in hypoxic pulmonary constriction in newborn pigs (13). An elegant study by Ungvari and Koller (57) showed that endothelin and prostaglandin H 2 /thromboxane A 2 mediate increased myogenic tone by potentiating Ca 2ϩ sensitivity of smooth muscle in skeletal muscle arterioles of spontaneously hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were reported earlier that provided evidence for a differential role of endothelium-derived factors on arterial tone in different pathophysiological conditions. Endothelial COX-mediated constrictor, likely to be thromboxane, was shown to be involved in hypoxic pulmonary constriction in newborn pigs (13). An elegant study by Ungvari and Koller (57) showed that endothelin and prostaglandin H 2 /thromboxane A 2 mediate increased myogenic tone by potentiating Ca 2ϩ sensitivity of smooth muscle in skeletal muscle arterioles of spontaneously hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…Piglet PRA (80-to 250-m diameter) were isolated, cannulated, and pressurized for continuous measurement of diameter according to our previously published methods (4,5,13,15,16,20). Briefly, PRA measuring Ͻ250-m diameter were dissected in oxygenated KrebsHenseleit buffer with the following millimolar composition: 118 NaCl, 25 NaHCO 3, 4.5 KCl, 1.2 MgCl2 ⅐ 6H2O, 1.2 KH2PO4, 11 dextrose, 2.5 CaCl 2 ⅐ 2H2O, and 0.026 EDTA equilibrated with 21% O 2, 5% CO2, and balance N2 to maintain pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…2, 19, 31, 73). In a related study, terbogrel, a combined thromboxane synthase inhibitor-receptor antagonist, attenuated pulmonary vasoconstriction in hypoxic piglets and increased the pulmonary vasodilator response to acetylcholine (31). Similarly, ozagrel, another thromboxane synthesis inhibitor, reduced PH and improved symptoms in a patient with portopulmonary hypertension (73).…”
Section: Serotonin (5-ht) and Serotonin Transporter (5-htt)mentioning
confidence: 95%